Diversity, Music, Theory, and the Neoliberal Academy - Sumanth Gopinath (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
This article is part of a special forum titled “Ethnic Diversity in Music Theory: Voices from the Field.” It begins with a narrative description of the author’s qualifying exam in tonal analysis for the Ph.D. program in music theory at Yale University. During the exam, which he failed, the author produced a hermeneutic interpretation of Brahms’s song “Der Gang zum Liebchen,” op. 48/1. The author then uses this experience as a point of departure from which to reflect upon issues of racial/ethnic diversity within Anglo-American music theory. Navigating between racial essentialism and race-blind universalism, the author offers critiques of statements by the Society for Music Theory (SMT) Diversity Committee, of official statements by the SMT leadership on diversity, and of the primarily Western musical orientation of current theory pedagogy. The article ends by situating academic diversity issues within the economic structure of the neoliberal university.